Aligning Total Quality Management, Continuous Improvement for Process Performance: A Review Approach - Ugwu, Kelechi (Publikasi Indonesia, 2023)
Research Purpose: The goal of this research is to explore the connection between total quality management, continuous improvement, and process performance. Research Method: The study explored a review of the literature approach on total quality management alongside other variables using recent investigations. Findings: This study identified a framework that connects total quality management, continuous improvement, and process performance. Research Contribution: This research contributed to developing a conceptual framework for performance, continuous process improvement, and total quality management. Research Restrictions/Implications: This study is an integrative evaluation of the prior research on the idea of overall quality management and its connection. Future researchers are urged to make use of descriptive surveys and empirical techniques to generalize their findings. Originality/Value: To reflect comprehensive quality management, continuous improvement, and process performance, this study created a conceptual framework and model. The author created a summary table to display earlier research on the subject, including authors, topics, countries, methodologies, and findings. In light of the aforementioned, the researcher filled a knowledge gap.